Benign disorders of the prostate: A histopathological study - Anim, J.T.; Ebrahim, B.H.; Sathar, S.A. (Annals of Saudi Medicine, 1998)
Although the medical literature contains adequate accounts of the pathophysiology of various benign prostatic disorders, it is often necessary to revisit these lesions, to reexamine the relationships between known benign lesions and more sinister, malignant disorders, in the light of new advances in our understanding of the processes. We carried out a histopathological review of prostatic surgical pathology material seen over a seven-year period in our hospital. Our findings show that benign enlargement of the prostate or benign prostatic hyperplasia (BPH) is initially fibromuscular in many cases, becoming glandulostromal with advancing age. While we found no relationship between prostatitis and age, individual gland necrosis tended to occur relatively early and correlated well with stromal repair, which we believe forms the basis of fibromuscular hyperplasia. Epithelial hyperplasia may result from glandular regeneration, and basal cell hyperplasia, papillary hyperplasia and cribriform hyperplasia all showed significant correlation with prostatic intraepithelial neoplasia (PIN). On the other hand, only cribriform hyperplasia showed correlation with atypical adenomatous hyperplasia (AAH), and also demonstrated an increase in incidence with advancing age. Our findings underline the positive relationships between benign events such as glandular necrosis with repair and epithelial hyperplasia, which may itself predispose to recognized premalignant lesions such as PIN.
Keywords: Adult; Aged; Article; Basal cell; Cell hyperplasia; Fibromuscular dysplasia; Histopathology; Human; Human tissue; Major clinical study; Male; Pathophysiology; Priority journal; Prostate hypertrophy; Prostatic intraepithelial neoplasia; Prostatitis; Tissue regeneration